2022
DOI: 10.3389/fphys.2021.789829
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and Soluble ST2 Are Associated With Recurrent Spontaneous Abortion in Early Pregnancy

Abstract: Normal pregnancy is related to the successful transition from type 1 cellular immunity to type 2 cellular immunity. Therefore, this study aimed to investigate whether there is abnormal expression of cytokines in the process of inducing Recurrent spontaneous abortion (RSA). Interleukin (IL)-33 is a new member of the IL-1 family, and ST2, as IL-33’s receptor, induced the production of type 2 cytokines. In this study, blood samples were collected from 19 non-pregnant women of normal childbearing age, 28 normal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…IL-33, is pivotal in regulating angiogenesis and inflammatory immune responses. Recent studies indicate considerably greater serum concentrations of IL-33 ( P < 0.05) and its receptor ST-2 ( P < 0.01) in patients with RPL compared to healthy controls [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-33, is pivotal in regulating angiogenesis and inflammatory immune responses. Recent studies indicate considerably greater serum concentrations of IL-33 ( P < 0.05) and its receptor ST-2 ( P < 0.01) in patients with RPL compared to healthy controls [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that IL-33 plays an essential role in several pregnancy-related diseases, including endometriosis, recurrent pregnancy loss and preeclampsia, etc. (Chen H. et al 2018 ; Fock et al 2013 ; Granne et al 2011 ; Miller J. E. et al 2017 ; Salker et al 2012 ; Zhao et al 2021 ). Unlike most of other cytokines, IL-33 can function either as a secreted cytokine or as an intracellular nuclear factor regulating gene expression (Bertheloot et al 2017 ; Cayrol et al 2018 ; 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with Cluster-2, Cluster-1 was significantly more enriched in the positive regulation of type 2 immune responses and positive regulation of IL-4 production. Successful pregnancy is closely associated with transition from type 1 to type 2 immune responses (Zhao et al, 2021) and IL-4 cytokine is a signature of type 2 immunity (Gause et al, 2020). Furthermore, GSEA showed that the FoxO signaling pathway was activated in Cluster-1, while the cell cycle and Wnt pathways were inhibited.…”
Section: Discussionmentioning
confidence: 99%